PERSEPSI TAMU TENTANG PELAYANAN RESEPSIONIS DI PREMIER BASKO HOTEL PADANG - NURSAL, MUTIA HERLINA; Chair, Ira Meirina; Yuliana, Yuliana (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2014)
This research was motivated by several things, among others, less polite reception staff and less friendly in serving guests.The purpose of this study was to describethe perceptions of a service receptionist at Premier Basko Hotel Padang in the review of the five service indicators are: reliability, responsiveness, assurance, empathy, and tangibles. This study is kuantitatif.Populasi in the research are Â Premier Basko Hotel Padang, amounting to 1704 people. The sampling are taken as incidental Â by 94 guests. The technique of collecting data using questionnaires Likert scale. Data were analyzed through descriptive analysis with the help of SPSS Program Version 16. The results showed that the perception of a service receptionist at Premier Basko Hotel Padang is quite good with an average value (mean) of 71.45. On the indicator reliability is in the category quite well with the average value (mean) of 15.40, the indicator of responsiveness in the category of less well with the average value (mean) of 12.32, the assurance indicators in the category of less well with the average value (mean) of 17.53, the indicator empathy is in the category of less well with the average value (mean) of 12.46, and the indicator tangiblesÂ physical evidence) is in the category of less average value (mean) of 13.72. Keywords : Perception, guest services, front office